2016
DOI: 10.1007/s10120-016-0633-1
|View full text |Cite|
|
Sign up to set email alerts
|

Conversion therapy for inoperable advanced gastric cancer patients by docetaxel, cisplatin, and S-1 (DCS) chemotherapy: a multi-institutional retrospective study

Abstract: Background Conversion therapy is an option for unresectable metastatic gastric cancer when distant metastases are controlled by chemotherapy; however, the feasibility and efficacy remain unclear. This study aimed to assess the feasibility and efficacy of conversion therapy in patients with initially unresectable gastric cancer treated with docetaxel, cisplatin, and S-1 (DCS) chemotherapy by evaluating clinical outcomes.Methods One hundred unresectable metastatic gastric cancer patients, enrolled in three DCS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 38 publications
8
77
3
Order By: Relevance
“…The reported incidence of postoperative complications after gastrectomy is 24% to 29% [30,32] , which is similar to that in patients undergoing conventional radical surgery for gastric cancer (20.9% in patients with D2 lymph node dissection and 28.1% in patients undergoing an extended operation with aortic lymph node dissection) (JCOG9501) [33] .…”
Section: Postoperative Complicationssupporting
confidence: 51%
See 1 more Smart Citation
“…The reported incidence of postoperative complications after gastrectomy is 24% to 29% [30,32] , which is similar to that in patients undergoing conventional radical surgery for gastric cancer (20.9% in patients with D2 lymph node dissection and 28.1% in patients undergoing an extended operation with aortic lymph node dissection) (JCOG9501) [33] .…”
Section: Postoperative Complicationssupporting
confidence: 51%
“…Yamaguchi et al [30] analyzed the treatment outcomes of 259 patients with stage IV gastric cancer and found that the MST of those who underwent R0 resection (41.3 months) was significantly better than that of patients who underwent R1 and R2 resection (21.2 months). Sato et al [32] evaluated the treatment outcomes of initially unresectable gastric cancer treated with docetaxel, cisplatin, and S-1 (DCS) chemotherapy in a clinical trial. Conversion therapy was achieved in 33 of 100 patients (33%), and R0 resection was performed in 28 (84.8%) patients.…”
Section: Predictive Factors For Long-term Outcomementioning
confidence: 99%
“…However, data from the eastern experience and the possibility of more extensive surgeries with low morbidity have led the physicians to be more aggressive in the treatment of metastatic disease. Curative outcomes have been reported with an R0 resection in potentially/marginally resectable cases, although they are initially metastatic diseases, referred to as conversion treatment (30)(31)(32). Although potentially resectable cases, such as single liver metastasis or 16a2-b1 paraaortic lymph node metastasis are technically suitable for surgical resection, we prefer preoperative chemotherapy followed by surgical resection.…”
Section: Management Of Metastatic Diseasementioning
confidence: 99%
“…In this way, no patients would be excluded from chemotherapy, and surgery would be performed in selected patients with a measurable response to chemotherapy [20]. New chemotherapeutic schedules and improved response rates have led to the development of several conversion therapy protocols that are currently under investigation in Eastern countries [21,22].…”
Section: Discussionmentioning
confidence: 99%